Donor-impurity related binding energy and photoinization cross-section in quantum dots: electric and magnetic fields and hydrostatic pressure effects - Barseghyan, M. G.; Kirakosyan, A. A.; Duque, C. A. (The European physical journal. B, Condensed matter physics, 2009)
We have studied the behavior of the binding energy and photoionization cross-section of a donor-impurity in cylindrical-shape GaAs-Ga 0.7 Al 0.3 As quantum dots, under the effects of hydrostatic pressure and in-growth direction applied electric and magnetic fields. We have used the variational method under the effective mass and parabolic band approximations. Parallel and perpendicular polarizations of the incident radiation and several values of the quantum dot geometry have also been considered. Our results show that the photoionization cross-section growths as the hydrostatic pressure is increased. For parallel polarization of the incident radiation, the photoionization cross-section decreases when the impurity is shifted from the center of the dot. In the case of perpendicular polarization of the incident radiation, the photoionization cross-section increases when the impurity is shifted in the radial direction of the dot. For on-axis impurities the transitions between the ground state of the impurity and the ground state of the quantum dot are forbidden. In the low pressure regime (less than 13.5 kbar) the impurity binding energy growths linearly with pressure, and in the high pressure regime (higher than 13.5 kbar) the binding energy growths up to a maximum and then decreases. Additionally, we have found that the applied electric and magnetic fields may favor the increase or decrease in binding energy, depending on the impurity position.